Use of Metaphors in Business News Reporting - Tolašová, Petra (Univerzita Pardubice, 2014)
This bachelor thesis focuses on figurative language with special regard to metaphor. The issue of metaphor is further explained in the thesis in compliance with the conceptual theory of metaphor and its principles. The role of a context in interpreting metaphor is also observed. The featured analysis focuses on the emergence of metaphor in business news reporting.
Užití metafor v novinové zprávě s obchodní tematikou
Keywords: figurative language; metaphor; conceptual theory of metaphor; role of the context; business news reporting; figurativní jazyk; metafora; konceptuální teorie metafor; role kontextu; novinové zprávy s obchodní tematikou